Saturable absorber mirrors for ytterbium mode-locked femtosecond lasers - Zinkiewicz, Łukasz Jan; Nawrot, Michał; Jasik, Agata; Pasternak, Iwona; Wasylczyk, Piotr (Photonics Letters of Poland, 2014)
We present a femtosecond, diode-pumped Yb:KYW laser configured with a range of saturable absorber mirrors, both commercially available and state-of-the-art structures. The laser performance is characterized for different output coupler (OC) transmission – for the typically used OC transmission between 0.5-10% the laser power increases with the increasing transmission but the spectrum gets narrower at the same time, resulting in longer pulses and the laser pulse peak power having a maximum. Full Text: PDF References C. Hönninger, R. Paschotta, M. Graf, F. Morier-Genoud, G. Zhang, M. Moser, S. Biswal, J. Nees, A. Braun, G.A. Mourou, I. Johannsen, A. Giesen, W. Seeber, U. Keller, "Ultrafast ytterbium-doped bulk lasers and laser amplifiers", Appl. Phys. B 69, 3 (1999). CrossRef A. Lagatsky, C. Brown, W. Sibbett, "Highly efficient and low threshold diode-pumped Kerr-lens mode-locked Yb:KYW laser", Opt. Expr. 12, 3928 (2004). CrossRef H. Liu, J. Nees, G. Mourou, "Diode-pumped Kerr-lens mode-locked Yb:KY(WO4)2 laser", Opt. Lett. 26, 1723 (2005). CrossRef P. Wasylczyk, C. Radzewicz, "Design and alignment criteria for a simple, robust, diode-pumped femtosecond Yb:KYW oscillator", Laser Phys. 19, 129 (2009). CrossRef S. Meyer, J. Squier, S. Diddams, "Diode-pumped Yb:KYW femtosecond laser frequency comb with stabilized carrier-envelope offset frequency", Eur. Phys. J. D 48, 19 (2008). CrossRef D. Kopf, G. Zhang, R. Fluck, M. Moser, U. Keller, "All-in-one dispersion-compensating saturable absorber mirror for compact femtosecond laser sources", Opt. Lett. 21, 486 (1996). CrossRef R. Paschotta, G. Spuhler, D. Sutter, N. Matuschek, U. Keller, M. Moser, R. Hovel, V. Scheuer, G. Angelow, T. Tschudi, "Double-chirped semiconductor mirror for dispersion compensation in femtosecond lasers", Appl. Phys. Lett. 75, 2166 (1999). CrossRef A. Jasik, P. Wasylczyk, M. Dems, P. Wnuk, A. Wójcik-Jedlińska, K. Reginski, Ł. Zinkiewicz, K. Hejduk, "A passively mode-locked, self-starting femtosecond Yb:KYW laser with a single highly dispersive semiconductor double-chirped mirror for dispersion compensation", Laser Phys. Lett. 10, 085302 (2013). CrossRef A. Schmidt, S. Rivier, W. Cho, J. Yim, S. Choi, S. Lee, F. Rotermund, D. Rytz, G. Steinmeyer, V. Petrov, U. Griebner, "Sub-100 fs single-walled carbon nanotube saturable absorber mode-locked Yb-laser operation near 1 µm", Opt. Expr. 17, 20109 (2009). CrossRef E. Rafailov, S. White, A. Lagatsky, A. Miller, W. Sibbett, D. Livshits, A. Zhukov, V. Ustinov, "Fast quantum-dot saturable absorber for passive mode-locking of solid-State lasers ", IEEE Photon. Technol. Lett. 16, 2439 (2004). CrossRef A. Jasik, J. Muszalski, J. Talalaev, M. Kosmala, K. Pierściński, M. Bugajski, "Low-temperature grown near surface semiconductor saturable absorber mirror: Design, growth conditions, characterization, and mode-locked operation", J. Appl. Phys. 109, 053101 (2009). CrossRef G. Sobon, J. Sotor, I. Pasternak, K. Grodecki, P. Paletko, W. Strupinski, Z. Jankiewicz and K. Abramski, "Er-Doped Fiber Laser Mode-Locked by CVD-Graphene Saturable Absorber", J. Light. Technol. 30, 2770 (2012). CrossRef